The Association Between Different Types of Dietary Carbohydrates and Colorectal Cancer: A Case-Control Study - Jonoush, Mona; Fathi, Soroor; Hassanpour Ardekanizadeh, Naeemeh; Khalatbari Mohseni, Golsa; Majidi, Nazanin; Keshavarz, Seyed Ali; Shekari, Soheila; Nemat Gorgani, Shiva; Torki, Saheb Abbas; Sotoudeh, Mahtab; Habibi, Fatemeh; Gholamalizadeh, Maryam; et al. (Frontiers in Nutrition, 2022)
Background Several factors such as genetics and dietary intake are involved in the development of colorectal cancer (CRC). Higher intake of dietary carbohydrates may be associated with an increased risk of CRC. This study aimed to investigate the association between different types of dietary carbohydrates and CRC. Methods This hospital-based case–control study was carried out from June 2020 to May 2021 on 480 randomly selected participants including 160 CRC patients and 320 healthy controls aged 35–70 years in Firoozgar hospital, Tehran, Iran. Dietary intake was assessed using Food Frequency Questionnaire (FFQ). Nutritionist IV software was used to determine the intake of calorie and various forms of dietary carbohydrates including total carbohydrate, simple sugar, glucose, fructose, galactose, sucrose, lactose, and maltose. Results The average daily intake of calorie, carbohydrates, sugar, glucose, fructose, sucrose, and maltose were significantly higher among CRC cases compared to the controls (All P < 0.05). The logistic regression found significant associations between CRC with dietary intake of carbohydrates (OR = 1.009, CI 95%: 1.003–1.01, P = 0.002), sugar (OR = 1.02, CI 95%: 1.01–1.03, P < 0.001), glucose (OR = 1.06, CI 95%: 1.01–1.11, P = 0.009), fructose (OR = 1.31, CI 95%: 1.19–1.43, P < 0.001), sucrose (OR = 1.19, CI 95%: 1.12.−1.25, P < 0.001), maltose (OR = 9.03, CI 95%: 3.93–20.78, P < 0.001), galactose (OR = 1.31, CI 95%: 1.07–1.6, P = 0.008), and lactose (OR = 1.009, CI 95%: 1.01–1.18, P = 0.02). This association remained significant after adjustment for sex and age (except for galactose and lactose), and additional adjustment for sleep, tobacco, and alcohol level, and further adjustment for calorie intake and body mass index (BMI) (except for glucose). Conclusions A positive association was found between CRC and dietary intake of carbohydrates, sugar, fructose, sucrose, and maltose. Following a low-carbohydrate, low-sugar diet may help prevent CRC. Future longitudinal studies are warranted to confirm these findings.